Accelerating Process Improvement Using Agile Techniques - Jacobs, Deb (CRC Press, 2009)
Accelerating Process Improvement Using Agile Techniques explains how agile programming is applied to standard process improvement. By applying agile techniques, IT organizations can speed up process improvement initiatives, minimize the resources these initiatives require, and maximize the benefits of process improvement. The book details step-by-step how to implement the Accelerating Process Improvement Methodology (APIM) and how to integrate APIM with various standard process improvement models and methodologies, including the ISO 9000 series, SPICE, TQM, SPIRE, PMBOK, and CMM/CMMI. Agile process improvement enables organizations to rapidly set strategic goals, meet a greater percentage of user requirements, and realize a quicker return on investment.